Using social media in corporate communication - Chaudhri, Vidhi A. (Henry Stewart Talks, 2022)
Corporate communication, Crisis communication, Social media, Stakeholder power, Lego, Shell, Kodaikanal, Greenpeace, Reputation management, Non-governmental organizations